Linguistic Strategies Used by Lawyers - Durant, Alan; Leung, Janny H.C (Language and Law, 2016)
Language plays an essential role both in creating law and in governing its implementation. Providing an accessible and comprehensive introduction to this subject, Language and Law:describes the different registers and genres that make up spoken and written legal language and how they develop over time; analyses real-life examples drawn from court cases from different parts of the world, illustrating the varieties of English used in the courtroom by speakers occupying different roles; addresses the challenges presented to our notions of law and regulation by online communication; discusses the complex role of translation in bilingual and multilingual jurisdictions, including Hong Kong and Canada; and provides readings from key scholars in the discipline, including Lawrence Solan, Peter Goodrich, Marianne Constable, David Mellinkoff, and Chris Heffer. With a wide range of activities throughout, this accessible textbook is essential reading for anyone studying language and law or forensic linguistics.